Praktik Filantropi dalam Upacara Kathina di Vihara Metta Palmerah - Nurhaliza, Elvira (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2025)
This research focuses on the practice of philanthropy in the Kathina ceremony at Vihara Metta Palmerah. With the aim of understanding what is the basis for Buddhists to practice philanthropy in the Kathina ceremony, as well as what forms of philanthropy are contained in the Kathina ceremony. The type of research used is descriptive qualitative with a field research method, and uses a sociological approach. Primary data was obtained through interviews with monastery administrators while secondary data came from related literature. Data collection techniques include observation and interviews. The researcher found that in the Kathina ceremony there is a sutta recitation, namely the Nidhikanda Sutta which means true treasure. The results showed that the Nindhikanda Sutta as a foundation for Buddhists to donate since the time of the Buddha.